Pemahaman Pelatih Kota Semarang tentang Teknik dan Keterampilan Mental Olahraga sebagai Proses Pencapaian Prestasi Olahraga - Candra, Adiska Rani Ditya; Setiawan, Arif; Hermawan, Hermawan; Sobihin, Sobihin (JOSSAE (Journal of Sport Science and Education), 2023)
Sports psychology factors as well as mental skill techniques are considered to have a significant influence on athlete performance. The purpose of this study was to measure the level of understanding of Semarang City coaches on mental factors that affect sports performance. In addition, the study also measured the coache's understanding of the technique of mental sports skills, namely Self-talk. The subjects in this study were the coaches of the city of Semarang with a total of 26 trainers. The method used in this study is a quantitative method with a descriptive approach to relative percentages. The results of the study show that from an understanding of mental skills which include psychological factors such as self-confidence, focus, motivation in the medium, low categories and there are some trainers who have very low understanding. While the sports psychology technique "Self-talk" is in the medium, high and very high categories. This is certainly a concern that it is time for coaches to be more serious and pay attention to sports mental training which is an important part of the sports training process and achieving better sports achievements